Design and Integration of Electronic Pressure Sensor for Stroke Patient - ZULHIBABULLAH, NUR ELMIRA ZALIA; ALI, AHMAD HADI (Enhanced Knowledge in Sciences and Technology, 2026)
Continuous hand grip pressure monitoring is frequently necessary for stroke rehabilitation to promote healing and avoid overexertion, but current systems are heavy, inflexible, or do not provide real-time feedback. This project aims to develop and integrate a wearable electronic pressure sensor for stroke rehabilitation. To acquire and process data, an Arduino Nano 33 IoT microcontroller was interfaced with a flex bend sensor that was set up in a voltage divider circuit. For real-time monitoring, sensor output was wirelessly transferred to an online spreadsheet and shown locally on a serial liquid crystal display. To determine sensor response, calibration behavior, and measurement stability, controlled weights and bending angles were applied during experimental testing. Both short and long sensors exhibit near-linear trends appropriate for calibration, and the results demonstrate a distinct and consistent inverse relationship between applied force or bending angle and output voltage. The longer sensor showed greater sensitivity because it has a larger active area. These findings confirm that the proposed system gives reliable and consistent pressure measurements. The prototype developed shows strong potential as a low-cost, non-intrusive tool for monitoring grip pressure during stroke rehabilitation. It also supports future use in wearable health monitoring systems.